Inhibition of quorum-sensing-mediated biofilm formation in Cronobacter sakazakii strains - Singh, Niharika; Patil, Amrita; Prabhune, Asmita; Goel, Gunjan (Microbiology-SGM, 2016)
The present study investigated plant extracts for their anti-quorum-sensing (QS) potential to inhibit the biofilm formation in Cronobacter sakazakii strains. The bioassay based on loss of pigment production by Chromobacterium violaceum 026 and Agrobacterium tumefaciens NTL4 (pZLR4) was used for initial screening of the extracts. Further, the effect of extracts on the inhibition of QS-mediated biofilm in C. sakazakii isolates was evaluated using standard crystal violet assay. The effect on biofilm texture was studied using SYTO9 staining and light and scanning electron microscopy. Among the tested extracts, Piper nigrum and Cinnamomum verum at 100 ppm resulted in 78 and 68% reduction in the production of violacein as well as blue-green colour in both biosensor strains. A higher inhibitory activity (>50 %) on biofilm formation in C. sakazakii was observed for Pip. nigrum and Cin. verum, whereas the other extracts possessed moderate (25-50 %) and minimal (<25 %) inhibitory activities. Further, the fluorescent and scanning electron microscopic images indicated a major disruption in the architecture of biofilms of tested strains by Pip. nigrum. This study points to the possibility of using Pip. nigrum and Cin. verum as inhibitor of QS-mediated biofilm formation by C. sakazakii that could be further explored for novel bioactive molecules to limit the emerging infections of C. sakazakii